ANALISIS KEMAMPUAN GURU AKIDAH AKHLAK DALAM PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) KURIKULUM 2013 DI MTs NEGERI KOTA PALOPO - arifuddin arifuddin (IAIN Bengkulu, 2020)
Abstract: The purpose of this study was to analyze the ability of teachers of the Islamic Morals in preparing the 2013 Curriculum Lesson Plan (RPP) in MTs Negeri Kota Palopo by using descriptive qualitative research methods. The qualitative descriptive method is a method used in research to analyze a problem that occurs and describe it based on data obtained from the results of research in the form of written or oral words of the problem being studied / traced. The author was conducted the research data collection by using 3 (three) instruments, namely observation, interviews, and documentation. The results showed that the ability of teachers of the Islamic Morals in preparing the 2013 Curriculum Lesson Plan (RPP) in the MTs Negeri Kota Palopo was categorized as